1986
DOI: 10.1289/ehp.8669287
|View full text |Cite
|
Sign up to set email alerts
|

A review of toxicology studies on cyanurate and its chlorinated derivatives.

Abstract: Chlorinated cyanurates are added to swimming pools as disinfectants. In the presence of water, these materials hydrolyze to yield cyanurate and hypochlorous acid. To evaluate the safety of exposure to these materials, a comprehensive testing program was undertaken. This review summarizes the results of acute and subchronic tests on chlorinated isocyanurates. Findings from acute, subchronic, reproduction, metabolism, mutagenicity, and chronic/carcinogenicity tests on cyanurate are also summarized. Results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 5 publications
3
33
0
Order By: Relevance
“…Cyanuric acid (s-triazine-2, 4, 6-triol) is related structurally to melamine. It is used as a stabilizer in outdoor swimming pools and hot tubs to minimize photodegradation of hypochloric acid (Hammond et al, 1986). Studies on the toxicity of cyanuric acid are limited, but since it is structurally similar, it likely behaves similarly to melamine.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanuric acid (s-triazine-2, 4, 6-triol) is related structurally to melamine. It is used as a stabilizer in outdoor swimming pools and hot tubs to minimize photodegradation of hypochloric acid (Hammond et al, 1986). Studies on the toxicity of cyanuric acid are limited, but since it is structurally similar, it likely behaves similarly to melamine.…”
Section: Introductionmentioning
confidence: 99%
“…These results show a higher sensitivity of fish cells when they are compared with other biological material tested, and thus, for example, Zeiger et al (1987) using the Ames test demonstrated that TCCA does not induce gene mutations. Hammond et al (1986) reported that there was no evidence of cyanurate-induced chromosomal aberrations chlorinated isocyanurates; and in chromosomal aberration tests in vitro, clastogenicity or polyploidy in CHL/IU cells was not induced in the absence or presence of an exogenous metabolic activation system (MHW 1997). However, no significant differences respects to control were obtained when RTG-2 cells were exposed to selected Oxone Ò concentrations, obtaining a maximal SSF value of 0.070.…”
Section: Discussionmentioning
confidence: 99%
“…sodium cyanurate) at 700 mg kg -1 and 2200 mg kg -1 doses in rats and mice, respectively, resulted in bladder calculi and bladder epithelial hyperplasia, with no other adverse effects. 43 In other studies, it was observed that dietary monosodium cyanurate administered in dogs for 6 months at 0.8% concentration produced no adverse effects, although at 8% for a longer period of 16 to 24 months it produced kidney fibrosis and fical dilation. 44 This was attributed to the low solubility of sodium cyanurate, due to which it precipitated at higher concentrations in urine, leading to renal dysfunction.…”
Section: Toxicity Caused By Co-crystal Formationmentioning
confidence: 90%